MELISSOPALYNOLOGICAL STUDIES OF AUTUMN HONEY SAMPLES FROM KHYBER PAKHTUNKHWA, PAKISTAN - S. Ahmad; M. Zafar; M. Ahmad; S. Zafar; M. Arfan; A. M. Khan; S. Sultana; M. A. Abbasi; S. Majeed (Journal of Animal and Plant Sciences, 2023)
The current study was carried out to investigate the geographical origin and botanical sources of 13 autumn honey samples collected from different areas of Khyber Pakhtunkhwa. For palynological analysis, samples were centrifuged and prepared according to the standard techniques of acetolysis. The study revealed the existence of diverse pollen in honey samples from 34 taxa, 31 genera and 18 different families. Honey was weighed, mixed with distilled water, and put in a centrifuge for analysis. Using light microscopy, pollen morphology and pollen counts were investigated. Identifications of pollen were examined from species to family level. Pollen grains of Saccharum spontaneum existed in every sample, revealing that these plants are distributed consistently all over the research area. In the analyzed samples, 04 were classified as dominant pollen, 08 accessory pollen and 01 isolated pollen. Unifloral and multifloral samples were recorded from the research area after analysis in the present study. Ziziphus jujuba and Saccharum spontaneum were abundant species within frequency classes. This study provides information about the flowering periods of plants, the conservation of bee flora, the importance of the autumn season regarding honey production, bee floral diversity, floral and the geographical occurrence of plants and honeybees. The diversity of bee-visiting plants led to promoting the annual yields of honey and providing opportunities for a business of beekeeping.
Keywords: Honey. Pollen. Khyber Pakhtunkhwa. Autumn season. Microscopy